The Role of Remittances in Migration Decisions to India with Special references after Bangladesh liberation movement in 1971: A Socio-Legal Study - Dr Joydeb Patra; Dr Tamal Gupta; Dr Prodipta Barman (The Bioscan, 2024)
This paper explores the role of remittances in shaping migration decisions from Bangladesh to India, particularly in the context of the Bangladesh Liberation Movement of 1971. The war, marked by widespread violence and socio-political upheaval, resulted in the displacement of millions of Bangladeshis who sought refuge in India. This study examines how remittances emerged as a vital source of financial support for families left behind, influencing their decisions to migrate or remain in their home country. By analyzing historical data, personal narratives, and the socio-economic impacts of remittances, the paper highlights the significance of financial resources in fostering both immediate survival and long-term community development. Furthermore, it discusses the lasting effects of the diaspora established during and after the conflict, emphasizing how remittances have contributed to economic stability and empowerment for many Bangladeshi families. Ultimately, this research underscores the complex interplay between migration, remittances, and socio-economic factors, offering valuable insights into the ongoing migration dynamics between Bangladesh and India.